Singapore’s LIFE program: Actuarial framework, longevity risk and impact of annuity fund return - KWONG, Koon Shing (Institutional Knowledge at Singapore Management University, 2017)
The Central Provident Fund (CPF) is a defined-contribution savings plan forming the key pillar of the pension system in Singapore. The CPF Lifelong Income For the Elderly (LIFE) program, which provides lifetime income for retirees, is a mandatory pension scheme for all Singapore residents. In this paper we construct an actuarial framework to analyze the LIFE program. We use this framework to study the plan payout outcomes with respect to changes in mortality and annuity fund return assumptions. We also examine the effects of some possible changes in the program on the payouts and bequests.